Education and disability trends of older Americans, 2000-2014. - Yuping Tsai (Journal of Public Health, 2017)
Background Trends in disability among older Americans has declined since the 1980s. The study examines whether the trend continues to decline and whether educational disparities exist in the prevalence of functional limitations. Methods I used the 2000--2014 National Health Interview Survey and included adults aged ≥65 years. Functional limitations was measured by three outcomes: the need for help with activities of daily living (ADLs) or instrumental activities of daily living (IADLs) and physical function limitations. I used a set of logistic models to estimate the average annual change rate of functional limitations. I examined whether the annual rate of change differed by education, age group and sex. Results During 2000--2014, the annual increase rate of ADL limitations was 1.7% (P < 0.001) and was 2.0% (P < 0.001) for physical function limitations; IADL limitation did not change significantly. All subgroups experienced an increase in ADL and physical function limitations except for adults with a more than high school education. The lower-educated group had a higher proportion and a higher annual rate of increase in all outcomes. Increasing trends in chronic conditions may contribute to the increasing trend in functional limitations. Conclusions The study highlighted a large educational disparity in late-life disability among older Americans.